2021
DOI: 10.3390/s21124128
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of RTT Fairness Problem in BBR Congestion Control Algorithm by Gamma Correction

Abstract: Google proposed the bottleneck bandwidth and round-trip propagation time (BBR), which is a new congestion control algorithm. BBR creates a network path model by measuring the available bottleneck bandwidth and the minimum round-trip time (RTT) to maximize delivery rate and minimize latency. However, some studies have shown that there are serious RTT fairness problems in the BBR algorithm. The flow with longer RTT will consume more bandwidth and the flows with shorter RTT will be severely squeezed or even starv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…To our knowledge, all published BBR variants blindly apply the fixed pacing rates of 1.25 and 0.75 when probing up for more available bandwidth and during probe down intervals, respectively, in the probebw phase. The abovedescribed pacing rates generate a persistent queue based on our experimental results and other studies' evaluations analysis [8,9]. Short RTT will be limited beforehand and progressively release bandwidth to the larger RTT flows since long RTT traffic has bigger RTprop values; therefore, their cwnd will be greater than short RTT flows'.…”
Section: Related Workmentioning
confidence: 91%
See 3 more Smart Citations
“…To our knowledge, all published BBR variants blindly apply the fixed pacing rates of 1.25 and 0.75 when probing up for more available bandwidth and during probe down intervals, respectively, in the probebw phase. The abovedescribed pacing rates generate a persistent queue based on our experimental results and other studies' evaluations analysis [8,9]. Short RTT will be limited beforehand and progressively release bandwidth to the larger RTT flows since long RTT traffic has bigger RTprop values; therefore, their cwnd will be greater than short RTT flows'.…”
Section: Related Workmentioning
confidence: 91%
“…After Google published the TCP-BBR, several studies have evaluated its performances under various network setups and conditions [15][16][17], while others have tried to improve various aspects of the BBR [8,[25][26][27][28].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Mathis et al [7] claimed that BBR opens a new era in congestion control and obsoletes Jacobson88. However, some evaluations [12][13][14][15][16][17][18] found that there are some problems in BBR, such as the unfairness when BBR and Reno/CUBIC share bottlenecks, the intraprotocol fairness, and RTT fairness. For the problem of the BBR algorithm, researchers are also making continuous efforts to obtain better performance by modifying some control parameters of BBR [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%